BSE, Vogelgrippe und Co.: die Bekämpfung von Tierseuchen und Zoonosen in der öffentlichen Wahrnehmung - Mettenleiter, Thomas C.; Reinking, Elke (2018)
Animal infectious diseases are not a product of modern animal husbandry, but public interest on outbreak, spread and control of animal infectious diseases has significantly increased recently. This is primarily focused on zoonoses, i.e. infectious diseases transmitted between animals and humans. Using recent outbreaks and control measures of „mad cow disease” BSE, avian influenza (“avian flu”) of subtypes H5N1 and H5N8 as well as the expansion in Eastern Europe of African Swine Fever as examples, the perception by the public, the rational basis for disease control options as well as the execution of evidence-based control measures will be discussed.